Immunology overview: tutorial : for international students - Климов, В. В. аллергология и иммунология 19540502 Владимир Васильевич (w. p., 2017)
This book combines current knowledge on basic immunology with an account of clinical comments. Since immunology is a very complex science, it requires a simplifield approach in order to be taught and understood. The book also contains some repetitions to remindthe reader of a variety of important components related to the immune system. For international students.